ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA INDUSTRI BARANG KONSUMSI YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2005-2009 - Fatmawati Fatmawati (JURNAL BISNIS STRATEGI, 2017)
This research performed to test the influence of Size, ROA, Current Ratio, and Sales Growth to ward Debt to Equity Ratio (DER) in consumer goods industries that listed on the Indonesian Stock Exchange period 2005-2009. The aimed of this research is to analyze the influence of Size, ROA, Current Ratio, and Sales Growth toward Debt to Equity Ratio (DER) in consumer goods industries that listed on the Indonesian Stock Exchange period 20052009.The population of this research were 37 companies that listed on the Indonesian Stock Exchange period 20052009. The sampling technique was purposive sampling with the criterias: (1) food and beverages companies, tobacco, pharmaceuticals and consumer goods listed in the BEi which exist throughout the study period from 2005 until 2009, and (2) food and beverages companies, tobacco, pharmaceuticals and consumer goods listed in the BE/ which submitted their data com plete with  the required information. The  data is obtained based on Indonesian Capital Market Directory (ICMD 2009) publication. The total sample are 23 companies that included in food and beverages,  tobacco, pharmaceuticals dan consumer goods companies.  The analyze technique used was multiple regression with least square equations and the hypothesis testing using t statistic for testing the partial regression coefficient and Fstatistic to test the effect together with the 5% level of confidence.The results showed that Size was significant positive to DER.  This research also found that ROA and Current Ratio were significant negative to DER. The other variable in this study is Sales Growth is not significant to DER.  Variables that have the most impact and significant effect to Debt to Equity Ratio (DER) are Size with coefficient value is 0,269; Current Ratio with coefficient value is 0,627, then ROA with coefficient value is 0, 185,. These findings indicated the things that need to be considered, either by the management company to manage the company, or by investors in determining investment strategy of the policy of Debt to Equity Ratio (DER) are Size, Current Ratio and ROA.